2015
DOI: 10.1001/jamapediatrics.2015.1797
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasonography Score to Evaluate Oxygenation and Surfactant Need in Neonates Treated With Continuous Positive Airway Pressure

Abstract: IMPORTANCE Lung ultrasonography (LUS) is a bedside technique useful to diagnose neonatal respiratory problems, but, to our knowledge, no data are available about its use for monitoring lung function or eventually guiding surfactant therapy.OBJECTIVE To determine the diagnostic accuracy of a neonatal-adapted LUS score to evaluate oxygenation and predict need for surfactant administration. DESIGN, SETTING, AND PARTICIPANTSProspective diagnostic accuracy study following STARD (Standards for the Reporting of Diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
491
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 329 publications
(514 citation statements)
references
References 29 publications
15
491
1
7
Order By: Relevance
“…We used a previously validated LUS score [13], adapted to our purpose, to monitor changes in the lung air/fluid ratio throughout the disease course. We performed follow-up LUS scans at set time intervals during the TTN course and were able to demonstrate that LUS and Silverman scores follow similar trends.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a previously validated LUS score [13], adapted to our purpose, to monitor changes in the lung air/fluid ratio throughout the disease course. We performed follow-up LUS scans at set time intervals during the TTN course and were able to demonstrate that LUS and Silverman scores follow similar trends.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, this LUS score is calculated based on 3 chest areas for each side (anterior, lateral, and posterior fields). A score of 0–3 points is given for each area according to basic LUS semiology; the total score ranges from 0 to 18 and is inversely correlated with lung aeration [13]. All LUS images were digitally recorded, anonymized and then centralized to the coordinating center, where they were reviewed by a senior independent ultrasonographer experienced in LUS (G.V.)…”
Section: Methodsmentioning
confidence: 99%
“…The accuracy of LUS in estimating the need for surfactant or respiratory support has already been analyzed [7,19,20]. In those studies, LUS was confirmed to be a good tool for prediction of the need for MV, being even better than chest X-rays [7].…”
Section: Discussionmentioning
confidence: 99%
“…After 28 DOL, if the patient was not on respiratory support, we would perform a LU every 2 weeks. We calculated the LU score as previously described by Brat et al by adding the score (0‐3) obtained in three areas of the thorax defined by the anterior axillary line, the posterior axillary line, and the mammary line (upper anterior, lower anterior, and lateral) with a total score range of 0 to 18.…”
Section: Methodsmentioning
confidence: 99%
“…Lung ultrasound (LU) has gained importance in the management of patients in the Neonatal Intensive Care Unit (NICU) as a safe and effective test to diagnose respiratory disease in newborns . It can be used to predict the need for respiratory support in the first hours of life or the need for surfactant administration in preterm infants . LU is reproducible and reduces the number of thoracic X‐rays performed in the NICU .…”
Section: Introductionmentioning
confidence: 99%